Securitising, Economising and Humanising Immigration: The Case of the Employment Permit System in South Korea. Issue 4 (1st October 2016) - Kim, Sookyung; Koo, Jeong-Woo
Abstract: Immigration poses a dilemma for host states. Embracing international migrants contributes to economic prosperity and enhances the national reputation as a guardian of human rights, while simultaneously triggering security concerns. How can a migrant-receiving state address this dilemma? Using the case of the Employment Permit System (EPS) enacted in South Korea in 2003, which was the first law to protect the basic rights of foreign workers, this paper examines how a nation-state optimises its immigration policies to at the same time satisfy the competing demands of security, economic prosperity and human rights. We argue that the Korean government's efforts to respond simultaneously to contradictory requirements have resulted in a decoupled policy structure in which gaps have been maintained between incorporating global norms of human rights and pursuing national interests such as economic growth and national security.